2021
DOI: 10.1177/23094990211042237
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical study on the effect of lengthening magnitude on spine off-loading in magnetically controlled growing rod surgery: Implications on lengthening frequency

Abstract: Purpose: To assess whether the magnitude of lengthening in magnetically controlled growing rod (MCGR) surgeries has an immediate or delayed effect on spinal off-loading. Methods: 9 whole porcine spines were instrumented using two standard MCGRs from T9 to L5. Static compression testing using a mechanical testing system (MTS) was performed at three MCGR lengthening stages (0 mm, 2 mm, and 6 mm) in each spine. At each stage, five cycles of compression at 175N with 25 min of relaxation was carried out. Off-loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…The implants led to significant load reduction of the spine so that the resulting stress shielding could possibly explain the later onset of osteoporosis. 30 However, their study had no follow-up, and one can only speculate on the long-term impact. McAfee et al and Dalenberg et al demonstrated in their preclinical canine models the negative influence of rigid spinal implants on BMD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The implants led to significant load reduction of the spine so that the resulting stress shielding could possibly explain the later onset of osteoporosis. 30 However, their study had no follow-up, and one can only speculate on the long-term impact. McAfee et al and Dalenberg et al demonstrated in their preclinical canine models the negative influence of rigid spinal implants on BMD.…”
Section: Discussionmentioning
confidence: 98%
“…Wong et al studied the biomechanics of vertebrae during MCGR surgery using an upright porcine spine under pressure. The implants led to significant load reduction of the spine so that the resulting stress shielding could possibly explain the later onset of osteoporosis 30 . However, their study had no follow-up, and one can only speculate on the long-term impact.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, metal debris issues led to a temporary suspension of the CE certification and an international advice to limit MCGR implantations [22,23]. Although MCGR does not require surgical lengthening, the repeated out-patient clinic visits still pose a burden on patients and families [19,24]. Moreover, due to its rigid nature, the device is difficult to contour to the spine, especially in the sagittal plane, and because the spine is immobilized and unloaded, this may lead to implant failure, stress shielding and stiffening of the spine [25].…”
Section: Introductionmentioning
confidence: 99%